Kosovo : Assessment of MFd's Technical Assistance Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
MFD technical assistance to Kosovo has been provided under special circumstances, since it is not a member of the IMF or of the World Bank. As a region within the former Federal Republic of Yugoslavia severely affected by the war with Serbia, Kosovo has been administered by the UNMIK on the basis of UN Security Council Decision 1244 of June 10, 1999. After the end of the war, the UNMIK requested technical assistance from the IMF. The IMF's Executive Board approved this request, and MFD began providing TA in late 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet